Tales From A Robotic World : How Intelligent Machines Will Shape Our Future - Floreano, Dario (Cambridge, Massachusetts : The MIT Press, 2022)
A glimpse into the future of intelligent machines, and a journey through the laboratories and researchers that are building them. The book offers a mix of fiction and nonfiction narrative: readers can "see" a world, a few decades away, where intelligent machines have become reality, and learn about the science brewing in today's labs and the technical and socioeconomic challenges, often through the words of scientists and entrepreneurs that make it happen.
Keywords: Technological forecasting; Technology--Social aspects; Robots--Social aspects